Innovative Metaphorical Design based on Parametric Technology - Jiale Tian; Li Jiale (E3S Web of Conferences, 2021)
This paper explores the application of metaphorical design in furniture design based on parametric technology. The semantics of designs were expressed by metaphors to enrich the ways of expression of furniture and meet customized needs. The methods, application and emotional expression of metaphorical design were analyzed, and the utilization of parametric technology in metaphorical design was explored based on case studies. Metaphorical design, as a means of furniture design, is a way of expression, or even an outcome of expression. Use of metaphorical design in the design process and parametric technology in manufacturing will allow the designers to turn conceptual ideas into real furniture pieces.